Clonal variation in apical dominance of Triplochiton scleroxglon K. Schum, in response to decapitation - Ladipo, D.O.; Leakey, R.R.B.; Grace, J. (1991)
Clonal trials with the West African hardwood Triplochiton scleroxylon, K. SCHUM. have indicated a positive relationship between stem size (height and diameter) and branching frequency (mean no. of branches per m of mainstem). As part of a programme of vegetative propagation and clonal selection, the present study with young plants examined clonal variation in apical dominance, the process which determines branching frequency. Young potted plants of five clones were decapitated by removing the apex and uppermost node. The plants were partially defoliated, leaving 4 to 6 leaves at the apical nodes. These plants were grown in a glasshouse at 25°C to 30 °c under experimental conditions testing:( i) two rates of fertilizer application (4.0'% .and 0.04'% liquid feed, NPK = 23:19.5:16); (ii) three rates of water application, ranging from field capacity to severe water stress (watering with 250 ml either every day, every three days or every 12 days); and (iii) two day lengths (10 hand 19.5 h). The length and number of lateral shoots formed on these decapitated plants were measured weekly to determine the percentage bud activity. In the f,i'rst four weeks after decapitation, percentage bud activity increased (Sprouting Phase) and, thereafter, it declined as dominance was re-imposed (Dominance Phase). Peak bud activity at week 4 was greatest with the higher rate of nutrient applkation under the daily and 3-day watering regimes, but was unaff,ected by daylength. During the Dominance Phase, bud activity remained high at the higher rat,e of nutrientappl;ication, under the 3 and 12- day watering regimes and under long days. The relative per.formance of different clones was consistent in all treatments. Of the three clones used in all experiments, clones 8038 and 8049 had similarly high activity (rank one or two) and clone 8053 displayed less activity. However, inconsistencies in clonal ranking occurred under the lowest rate of watering. Responses to decapitation can thus be used as a robust indicator of genetic variation in apical dominance, provided care is taken: (i) to avoid extreme environmental conditions; and (ii) to maintain uniformity in the morphological (height, no. of leaves etc.) and physiological state (eg water and nutrient status) of the plants and their growing environment (especially light).